จากภาพยนตร์ พลเมืองจูหลิง ถึง จูหลิงในแบบพลเมืองอาเซียน - ประพัฒน์ทอง, พลวัฒ (Connexion: Journal of Humanities and Social Sciences, 2014)
The documentary movie ‘Citizen Juling’ featured political, cultural, historical and ethnic conflicts amongst people in the South of Thailand, the conflicts also facing those in the North of Thailand. The story, narrated according to local political situations, attempted to present varied views of different groups of people towards conflicts having arisen from historical, religious, ethnic and cultural issues prevalent in ASEAN member countries. This article was based on a cultural study devoted to understanding ‘strangers in our land’, a phenomenon of change encountered by the ASEAN countries in their course towards an ASEAN community.